2015
DOI: 10.15376/biores.10.4.7419-7433
|View full text |Cite
|
Sign up to set email alerts
|

Glulam Properties of Fast-growing Species Using Mahogany Tannin Adhesive

Abstract: Manufacturing glued laminated timber (glulam) can help overcome the limited availability of large-sized timber, and the use of bio-adhesives may resolve environmental problems associated with synthetic adhesives containing high formaldehyde contents. Tannin adhesive is a bio-adhesive that can be used as alternative glue in the manufacture of glulam. The purpose of this study was to determine the physical and mechanical properties of glulam made with mahogany (Swietenia sp.) tannin adhesive and wood from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
0
19
0
10
Order By: Relevance
“…The MOE of laminated composite made with tannin adhesive was lower than that of the solid wood. The MOE of laminated composite (4096.43 ± 955.76 MPa) was also lower than the MOE of glulam (4726.61 MPa) made from jabon and sengon wood with mahogany adhesive (Lestari et al 2015). Based on Supartini (2012), the MOE of laminated composite made from jabon with mangium adhesive was slightly lower than that of jabon cross laminated timber with MDI (4,824.87 ± 0.18 MPa).…”
Section: Modulus Of Elasticitymentioning
confidence: 87%
See 1 more Smart Citation
“…The MOE of laminated composite made with tannin adhesive was lower than that of the solid wood. The MOE of laminated composite (4096.43 ± 955.76 MPa) was also lower than the MOE of glulam (4726.61 MPa) made from jabon and sengon wood with mahogany adhesive (Lestari et al 2015). Based on Supartini (2012), the MOE of laminated composite made from jabon with mangium adhesive was slightly lower than that of jabon cross laminated timber with MDI (4,824.87 ± 0.18 MPa).…”
Section: Modulus Of Elasticitymentioning
confidence: 87%
“…The reactivity can be affected by the bark freshness, source of wood, tree habitat, and extraction methods (Achmadi 1990). Tannin extract accounted for 198.3 g of 1 kg mangium bark or 19.83%, and it had a Stiasny number of 83.48% (w/w), which was higher than that for mahogany extract (79.7%; Lestari et al 2015). This finding indicated that mangium extract has a high amount of reactive polyphenol available for polymerization and would be appropriate for use as a resin.…”
Section: Chemical Analysis Of Mangium Tannin Extractmentioning
confidence: 88%
“…To determine the delamination of specimens extracted from glued laminated timber beams, 6 specimens with 7.5 x 6.0 x A cm (length, width and A = thickness) were drawn in parallel to the fibers, using the methodology described by Lestari et al (2015).…”
Section: Properties Of the Glued Laminated Timber Beamsmentioning
confidence: 99%
“…However, the present use of commercial tannins for leather manufacturing [122], and beverages [123] limits their availability for other industrial resins. Despite this, tannins have been the subject of extensive research, leading to the exploration of a wide range of adhesive applications [14,101,124]. Attempts have been made to commercialize tannin-based adhesives with limited success [125].…”
Section: Tanninmentioning
confidence: 99%
“…Glulam from three layers of lamina has been manufactured by using a mahogany tanninadhesive system, composed of tannin extract and formaldehyde [124]. The results showed that the adhesive was on par with the conventional adhesive for glulam manufacturing regarding mechanical and physical properties, and had low formaldehyde emission.…”
Section: Tanninmentioning
confidence: 99%